Respuesta :

Answer:

[tex]{ \rm{3 {x}^{2} + 2x - 4 = 0 }}[/tex]

• let's use the quadratic formular to solve the quadratic equation given.

• Considering general quadratic equation; ax² + bx + c = 0

• therefore;

[tex]{ \tt{x = \frac{ - b \pm \sqrt{ {b}^{2} - 4ac } }{2a} }} \\ [/tex]

  • a is 3
  • b is 2
  • c is -4

• substitute following the mathematical operation rules:

[tex]{ \rm{x = \frac{ - 2 \pm \sqrt{ {2}^{2} - (4 \times 3 \times - 4) } }{(2 \times 3)} }} \\ \\ { \rm{x = \frac{ - 2 \pm52}{6} }} \\ [/tex]

• split the values:

[tex]{ \rm{either \: \{x = \frac{ - 2 + \sqrt{52} }{6} \} \: \: or \: \: \{x = \frac{ - 2 - \sqrt{52} }{6} \} }} \\ \\ { \rm{either \: \{x = 0.87 \} \: \: or \: \: \{x = - 1.54 \}}}[/tex]